ROLE OF MEDICINAL HERBS IN THE MANAGEMENT OF AMAVATA (RHEUMATIC ARTHRITIS): AN AYURVEDIC APPROACH - Kumawat, *Meenakshi; Damor, Jyoti; kachchhwaha, Jaya; Sharma, Mayukh; Vishnoi, Harish; Singh, Chandan (International Journal of Ayurveda and Pharma Research, 2018)
Rheumatoid Arthritis (known as Amavata in Ayurveda) is an autoimmune disease that causes chronic inflammation of the joints. Autoimmune diseases are illnesses that occur when the body's tissues are mistakenly attacked by their own immune system. Patients with autoimmune diseases have antibodies in their blood that target their own body tissues, where they can be associated with inflammation. Because it can affect multiple other organs of the body, Rheumatoid Arthritis is referred to as a systemic illness and is sometimes called rheumatoid disease. According to the Ayurvedic system of medicine the formation of endotoxins called Aam. Aam is basically undigested and unassimilated food of our body. Aam also results from leading an unhealthy life style, ingestion of state food, defrosting and reheating eatables, mental tension and stress. the herbs have the potential to treat symptoms of RA like inflammation and pain other than that, it also treats arthritis at immune and free radical level. These herbs are known for their immunosuppressive action, anti-inflammatory action, analgesic action and antioxidant action. It was concluded that RA can be cured completely or manage well with Ayurveda medicines and Panchakarma without any side effects.